The Red Thread of the Gnostic Church´s Bishops "Master Huiracocha Tradition" in Venezuela - MORALES RONDON, Victoria (Utopía y Praxis Latinoamericana, 2021)
The Rosicrucian Antiqua Fraternity of Venezuela houses the ancient Gnostic Church Tradition Master Huiracocha. It shares the same Christian apostolic lineage with other churches that declare themselves successors of ancient schismatic churches such as the Gnostics, the Cathars and the order of the Elus Cohen. The degrees are: Acolyte, Deacon, Priest, Bishop, Archbishop and Patriarch. The religious texts on which its liturgy is based are: the Holy Bible, the Pistis Sophia and the Liber AL vel Legis. The epicospal succession has been maintained through a controversial red thread that has its origins in Europe.